Addressing challenges in simultaneous implementation of regional head elections during the Covid-19 Pandemic - Kusdarini, Eny; Sunarso, Sunarso; Suharno, Suharno; Nasiwan, Nasiwan (Universitas Negeri Yogyakarta, 2023)
This study describes and evaluates the implementation of the simultaneous continuation of local elections in 2020 and the challenges faced during the ongoing COVID-19 pandemic in Indonesia. This pandemic has disrupted the economic and societal order, including the governance aspect, which encompasses the electoral process for selecting local leaders to continue the previous simultaneous local elections held in the preceding year. The Indonesian government has decided to proceed with the local elections that were initially postponed. Several other countries worldwide have also chosen to hold general elections, although some countries have opted to delay them. This study adopts an ex post facto research design with a qualitative approach. The research object is implementing the simultaneous continuation of local elections in Bantul Regency, DIY Province, in 2020, with the selection of research subjects conducted purposively. Data collection is carried out through interviews and documentation. This paper highlights various challenges encountered during the implementation of local elections in 2020 while Indonesia was still amid the COVID-19 pandemic.